Holy Blood Holy Grail - Baigent, Michael; Leigh, Richard, 1943-2007; Lincoln, Henry (New York, NY Delta Trade Paperbacks, 1983)
Is the traditional, accepted view of the life of Christ in some way incomplete?

• Is it possible Christ did not die on the cross?
• Is it possible Jesus was married, a father, and that his bloodline still exists?
• Is it possible that parchments found in the South of France a century ago reveal one of the best-kept secrets of Christendom?
• Is it possible that these parchments contain the very heart of the mystery of the Holy Grail?

According to the authors of this extraordinarily provocative, meticulously researched book, not only are these things possible — they are probably true! so revolutionary, so original, so convincing, that the most faithful Christians will be moved; here is the book that has sparked worldwide controversey.
- Part One the mystery
1- Village of mystery
2- The Cathars and the great Heresy
3- The Warrior - Monks
4- Secret Documents

- Part Two the secret society
5- The Order Behind the scnes
6- The Grand masters and the underground stream
7- Conspiracy through the centuries
8- The secret society today
9- The Long- haired monarchs
10- The Exiled Tribe

- Part Three the Bloodline
11- The Holy Grail
12- The Priest - king who never ruled
13- The Secret the Church Forbade
14- The Grail Dynasty
15- Conclusion and portents for the future
Keywords: Templars; Grail; France - History - Miscellanea; Rennes-le-Chateau (France)